Guidelines for keeping pace with innovation and tech adoption : how to respond when competition, your customers, and automation come knocking - Schindler, Esther, 1958- (O'Reilly Media, 2017)
There are many tech innovations today for companies looking to stay competitive and be more productive. From new programming languages and tools like Hadoop to processes like DevOps, the choices are tempting. Which ones are genuine game changers? Which are right for your business? This report explores guidelines that can help you make crucial "right item, right time" decisions, and assist in the integration of new technology into existing business processes. Author Esther Schindler explains that even when the item truly is exciting, committing too soon or too late is equally risky. This report will help you navigate the tech adoption maze with advice and eye-opening examples from several executives and consultants intimately involved with this process. You'll learn a measured approach for recognizing when and how to implement a particular technology change. Discover where your company stands on the technology adoption curve Measure the promise of a new technology or process against your company goals Examine how the change will impact your company's existing processes, technology, and teams Sell the change across the company's ecosystem, from employees and customers to strategic partners and vendors Make the transition slowly by introducing the new tech to only one department or product line Consider a formal change management process to execute the change Esther Schindler is a longtime tech industry journalist who has translated geek-talk into English since 1992. She loves to explain how technology indeed can improve the quality of life. Find her on Twitter at @estherschindler.